Parental perceptions of bladder dysfunction in children with symptomatic joint hypermobility. Issue 4 (29th November 2021) - Veriki, Marianna; Coomer, Annette; V. Simmonds, Jane
Abstract: Children with symptomatic joint hypermobility (SJH) report chronic pain, fatigue, and joint instability as their main symptoms. Symptoms can extend beyond musculoskeletal and include lower urinary tract dysfunction (LUTD). There are no studies exploring parent‐perceived quality of life (QoL) in children with LUTD, or strategies used to manage symptoms in this population. Our online cross‐sectional survey assessed parents of 6–18‐year‐olds via two UK charitable organizations. It included the Pediatric Incontinence Questionnaire (PinQ), the Dysfunctional Voiding Symptom Score, and questions exploring treatments and efficacy. Sixty‐seven parental questionnaires were analyzed. The majority of children were white females (95%, n = 64). Urgency (97%, n = 65) and enuresis (41.7%, n = 28) were the most frequently reported symptoms. The PinQ questionnaire showed that children were emotionally distressed by LUTD. Twenty‐nine parents (43%, n = 29) reported pharmacotherapy as the most effective treatment. Few had accessed other treatments such as physiotherapy (16%, n = 18). Most parents reported that overall treatment did not meet their expectations. This study highlights that parents perceive LUTD as having a great impact on their child's QoL. There is need for education among clinicians about LUTD and hypermobility‐related disorders, and for development and evaluation of treatments.